2005
DOI: 10.1016/j.jvs.2005.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular repair of abdominal aortic aneurysm in octogenarians: An analysis based on EUROSTAR data

Abstract: Our study supports that EVAR might be considered when treating elderly patients, provided their aneurysms are anatomically suited for the endovascular technique. The risk for late complications compared with open repair may be outweighed by a lower early mortality as well as a shorter time for physical recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
2
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 33 publications
4
64
2
3
Order By: Relevance
“…These associations were expected and have been reported previously. [17][18][19][20][21] Nevertheless, the influence of the ASA score on midterm survival among RBWH patients was notably strong, with 5-year survival rates for ASA 2, 3, and 4 individuals of 90.5%, 64.3%, and 23.1%, respectively. Similarly, Boult et al 17 found the ASA score was the most powerful predictor of midterm survival among the ASERNIP-S audit patients.…”
Section: Discussionmentioning
confidence: 99%
“…These associations were expected and have been reported previously. [17][18][19][20][21] Nevertheless, the influence of the ASA score on midterm survival among RBWH patients was notably strong, with 5-year survival rates for ASA 2, 3, and 4 individuals of 90.5%, 64.3%, and 23.1%, respectively. Similarly, Boult et al 17 found the ASA score was the most powerful predictor of midterm survival among the ASERNIP-S audit patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent actuarial studies have shown that a person alive at 80 can expect to live for another 9.5 years while a person alive at 90 can expect to live another 5 years [10], making a conservative approach for symptomatic arterial disease unpalatable for most elderly patients. Ironically, elective operation is the most important measure to prevent post-operative morbidity and mortality (particularly in AAA disease) [11] and conservatism may lead to older patients not being treated early enough, thus presenting as an emergency [12]. This prompted us to analyse our approach to management of elderly patients and to compare our complication rates in our open and endovascular cases between the elderly patients and younger cohort, ultimately to determine whether we should use age as an influential factor in making a management decision.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 There are many reports with large numbers of patients suggesting that EVAR in octogenarians is acceptably safe and effective. 3,10,11 Some observational studies do report successful management of nonagenarians with AAA using EVAR, but such reports tend to report few cases, and thus, it is difficult to draw reliable conclusions. 12,13 In addition, a true successful outcome from EVAR should be interpreted with reference to the alternative outcome under conservative management.…”
Section: Introductionmentioning
confidence: 99%